Analisis Penerapan Shift Kerja Karyawan Pada Main Kitchen Best Western Papilio Hotel Surabaya - Salfa Mei Dianawati; Lilis Sulandari; Sri Handajani; Niken Purwidiani (Journal of Creative Student Research, 2023)
Shift work is a system for organizing human resource activities in a particular industry with the aim that the human resources in it can work according to a predetermined schedule. Main kitchen is the main kitchen section that handles a variety of sauces, stocks, and various main courses. This study aims to analyze the application of employee work shifts in the main kitchen of Best Western Papilio Hotel Surabaya. This research is a qualitative descriptive research. Data collection was done by field observation, interview with 1 sous chef, and giving questionnaires to 7 employees in the main kitchen. The data obtained were analyzed descriptively.The results showed: 1) The implementation of employee work shit in the main kitchen of Best Western Papilio Hotel Surabaya is in accordance with established company regulations and government regulations. The application in the main kitchen of Best Western Papilio Hotel Surabaya includes: working for 8 hours a day with a maximum break time of 1 hour; there is a difference in work limits between permanent and daily contract employees so that in making schedules it is always done in the middle of the month and the beginning of the month so that there is a regularity of schedules; there are 3 work shifts namely morning, afternoon and night with a pattern of 5 working days 1 day off in one week.